Reliability and Validity of the Patient-Specific Functional Scale in Community-Dwelling Older Adults. Issue 3 (July 2019) - Mathis, Ruth Ann; Taylor, J. David; Odom, Brian H.; Lairamore, Chad
Abstract : Background and Purpose: Clinical measurement of physical function that is both specific to the individual and generates comparable outcome data is a fundamental need in physical therapy examination. The Patient-Specific Functional Scale (PSFS) has been found to be a reliable and valid measure of physical function in patients with musculoskeletal disorders and may have applications for other patient populations. However, the reliability and the validity of the PSFS have not been evaluated in older adults. The purpose of this study was to investigate the reliability and the validity of the PSFS in community-dwelling older adults. Methods: Thirty-one community-dwelling older adults (11 males, 20 females), mean age = 81.1 (8.3) years, were included. Participants completed the PSFS, Lower Extremity Functional Scale (LEFS), Activity-specific Balance Confidence Scale (ABC), Short Physical Performance Battery (SPPB), Berg Balance Scale, and the Timed Up and Go on 2 separate days, 48 hours apart. Assessment scores were compared between testing days and reliability was analyzed using the intraclass correlation coefficient (ICC) and minimal detectable change (MDC). Validity of the PSFS was assessed by comparing initial scores with the other measures using the Pearson correlation coefficient, scatter plots, and Bland-Altman plots. Results: The ICC and the MDC for the PSFS were 0.82 (95% confidence interval = 0.67-0.91) and 2.8, respectively. Significant correlations ( P < .05) were found when the PSFS was compared with the ABC ( r = 0.68), LEFS ( r = 0.81), and SPPB ( r = 0.37). Bland-Altman plots and 95% limits of agreement (LOA) using z scores indicated considerable agreement between the PSFS versus the ABC (LOA =−1.6 to 1.6), LEFS (LOA =−1.2 to 1.2), and SPPB (LOA =−2.1 to 2.1). Conclusion: The PSFS is a reliable and valid measure of physical function in community-dwelling older adults. A change of 2.8 or greater on the PSFS suggests a true change in physical function in this population.